Myelitis: A Common Complication of Tuberculous Meningitis Predicting Poor Outcome - Jiang, Yuxuan; Xu, Xiangqin; Guo, Zhuoxin; Liu, Yuxin; Lin, Jiahao; Suo, Lijun; Jiang, Ying; Liu, Bo; Lu, Tingting (Frontiers in Neurology, 2022)
Background: Myelitis is an important complication in patients with tuberculous meningitis (TBM). However, a paucity of publications exist on the spectrum of neurological and magnetic resonance (MR) imaging findings of TBM-related myelitis. The risk factors and prognosis of myelitis in TBM patients are not fully understood. Therefore, our study aims to identify the risk factors, clinicoradiological features and prognostic impact of myelitis for TBM patients. Methods: We conducted a retrospective study in our institution. TBM patients who were consecutively admitted during the period of August 2015 to December 2019 were included. We reviewed the demographic characteristics, clinical, laboratory and MRI findings, and clinical outcomes of all of the included patients. The diagnosis of myelitis was identified by a hyperintensity on T2-weighted images that was associated with cord edema, enlargement, and marginal or no enhancement on contrast-enhanced images. Results: A total of 114 patients were included. Myelitis occurred in 19 (16.7%) patients, five of whom paradoxically developed myelitis. In the MRI findings, the hyperintensities on T2-weighted images involved more than 3 spinal cord segments. Myelitis was often combined with other forms of spinal cord injury, including 10 patients (52.6%) with spinal meningeal enhancement, 7 (36.8%) with enlargement of the central canal of the spinal cord, 6 patients (31.6%) with tuberculoma, 4 patients (21.1%) with arachnoiditis and 1 patient (5.3%) with cerebrospinal fluid loculations. no patients with paradoxical myelitis were complicated with spinal meningeal enhancement and arachnoiditis, while 4 patients were complicated with enlargements of the central canal of the spinal cord. In multivariable analysis, A grade III disease severity on admission (p=0.003, OR=8.131, 95%CI:2.080-31.779) and high CSF protein (p=0.033, OR=1.698, 95%CI: 1.043-2.763) were independent risk factors for myelitis. myelitis (p=0.030, OR=13.297, 95%CI: 1.283-137.812) and disturbance of consciousness (p=0.042, OR=12.625, 95%CI: 1.092-145.903) were independent risk factors for poor outcomes. Conclusion: Myelitis was a common complication of tuberculous meningitis and independently predicted a poor outcome. A grade III disease severity and high CSF protein on admission were independent risk factors for myelitis. Paradoxical myelitis was rarely complicated with spinal meningeal enhancements and arachnoiditis, indicating that the immune reaction may play a dominant role.